Optimization of Samapta Unit Turjawali Patrol in Reducing the Crime of Theft in the Demak Police Jurisdiction Area - Hafiz, Daffy Muhammad (Police Studies Review, 2024)
The purpose of this research is to find the obstacles that result in the suboptimal patrol unit of the Samapta unit in suppressing the crime of theft in the jurisdiction of the Demak Police. The Demak Resort Police area was chosen as the research area. Demak Regency, situated approximately 25 kilometers east of Semarang City, falls under the legal jurisdiction of Demak Police Resort, spanning from 6°43'26'' to 7°09'43''S and 110°48'4''East. The research will use a qualitative approach, utilizing qualitative research methods, particularly an exploratory qualitative approach.The limited provision of fuel budget for patrol activities is one of the striking things. In addition, the number of patrol personnel that there are only 4-5 personnel per patrol means that not all or even 50% of the Demak area is out of reach of the Demak Police Samapta Unit Patrol Unit. Based on previously processed data and information, the implementation of patrols by the Samapta Unit of the Demak Police as a preventive step in minimizing the crime of theft is considered not to be effective. In analyzing the research problems, it used optimization concepts, patrol, POAC and 4M management theory, and SWOT theory are used to analyze influencing factors. This research used a qualitative approach, as well as field research data collection through interviews, observation, and document study. The result of the research is the implementation of patrol by Samapta Unit Demak Police for the prevention of motor vehicle theft is rated not optimal as it’s not reached the ideal conditions as stipulated by the regulations. This includes the condition of organizational resources, where personnel quality and quantity are still less than ideal, the fuel budget is insufficient to meet patrol needs, methods that are not varied, and several patrol tools that are in poor condition. In the implementation of patrols, planning is still not specific to the highest crime rate which one is theft by weighting, leadership lack direction, patrol routes are not varied enough, the use of patrol vehicles is not evenly distributed, and people who are less aware of the safety of their environment. Condition that are hoping for in the future that Patrol Unit of Samapta Demak resort police could press the number of vehicle theft with optimal and effective to help protect the safety of the citizen in Demak Regident. With a new concept of planning, organizing, actuating, and controlling could improve the performance from Patrol Unit of Samapta Demak Resort Police. Utilization of personel, facilities, and infrastructure are expected to also be use as optimal as it be to cover existing deficiencies and optimizing existing of patrol implementation. The forthcoming suggestions for the leaders of Demak Resort Police are implementing measures such as providing comprehensive training or certification for patrol members with respect to their roles and responsibilities, augmenting personnel allocation for efficient task distribution, and enhancing the fuel budget to expand the patrol area and execution. These measures aimed at attaining more favorable outcomes and maximizing operational effectiveness.